Method of quality improvement and economic efficiency of pharmacotherapy for community-acquired pneumonia and its utility in Ukraine health-care facilities - A.B. Zimenkovsky (Danylo Halytsky Lviv National Medical University, 2020)
Aim. Development of a method quality improvement and economic efficiency of pharmacotherapy for community-acquired pneumonia with the possibility of its further use in Ukraine health care facilities.